Study of normal ECGs of healthy Nepalese Medical personals without any apparent Medical illness - Nepal, Manoj; Upadhyaya, AB; Tibrewala, L.P.; Regmi, PR; Acharya, K; Shah, AK; Khanel, HH; Shrestha, S; Rajbhandari, S (Nepalese Heart Journal, 2003)
To find the normal electrocardiographic duration, intervals, and axis in a healthy group of Nepalese doctors, nurses and medical representatives and to see if these figures differ from the standard values described in the textbooks and literature.